Corticomedullary mixed tumour resembling a small adrenal gland-involvement of cancer stem cells: case report - Duan, Lian (BMC Endocr Disord, 2017)
BACKGROUND: Adrenal corticomedullary mixed tumours are very rare. Its mechanism is rarely reported. Here we report the first case of a corticomedullary mixed tumour resembling a “small adrenal gland” with distinct arrangement of the cortical and medullary layers. We further hypothesize regarding the tumorigenic mechanism of this tumour. CASE PRESENTATION: A 58-year man had been diagnosed with diabetes and hypertension for 3 years. His 24-h urine vanillylmandelic acid (VMA) levels were slightly elevated. An abnormal circadian cortisol rhythm was noted, and his cortisol levels were not suppressed by dexamethasone. Abdominal computed tomography (CT) revealed a right adrenal gland lesion (diameter, 30 × 38 mm), while an enhanced CT showed enhancement and hypervascularization. The tumour was positive for adrenocorticotropic hormone, chromogranin A (CGA), and steroidogenic factor-1 (SF-1) on the tumour surface. Acetaldehyde dehydrogenase 1(ALDH1), CD44, CD133, Nestin, Nerve growth factor receptor (NGFR), and Sex determining region y-box 9(SOX9) staining were positive. Although administration of medications for diabetes and hypertension was stopped until surgery was performed, the blood sugar level and blood pressure were maintained after surgery. CONCLUSIONS: This is the first report about a possible mechanism by which cancer stem cells induce adrenal corticomedullary tumours.